If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z + -2t = 1 Reorder the terms: -2t + z = 1 Solving -2t + z = 1 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-1z' to each side of the equation. -2t + z + -1z = 1 + -1z Combine like terms: z + -1z = 0 -2t + 0 = 1 + -1z -2t = 1 + -1z Divide each side by '-2'. t = -0.5 + 0.5z Simplifying t = -0.5 + 0.5z
| y+z=-2 | | 3x-4=x+13 | | x+2y=5 | | -x-y+2z=4 | | 40=7t-2 | | 3n-12=-6 | | 4y+1=12 | | -x-y+2z-4t=4 | | 6x-9=27 | | 5x-6=4x+2 | | -5=x-3-7 | | 3n-6=51 | | 7-3p+4=14 | | -7=6v-4-5v | | 2x-18=-12 | | -6n+7n=8 | | 1+2n+3=12 | | 8x+4x=12 | | -24=6m+6m | | -9=n+2n | | (nx-5)-7=(3x-n)-15 | | -3=-3r+6r | | -5x-7-x=17 | | 19-h-h=13 | | -8=k-8-k | | -1-8r-5=18 | | -22=-6b-5b | | 0=-p-p | | -23=-7+6x-4 | | 4k+k=-20 | | 3m-4-4=4 | | -11=-8n-3n |